(untitled) (Research, Society and Development, 2021)
Had as to identify the perception of pregnant adolescents about prenatal consultations in a teaching hospital. Descriptive, exploratory study with a qualitative approach, carried out in the prenatal outpatient clinic of a University Hospital in the City of Recife-PE and approved by the Ethics and Research Committee the place of study. Pregnant women aged 10-19 years, where the World Health Organization circumscribes adolescence to the second decade of life (10 to 19 years old), with at least three prenatal consultations were included and excluded those who, even after all the explanations, did not understand the objective of the research. Five pregnant women from 12 to 19 years of age participated in the research. Most were single (n = 05), five are still studying, one had completed high school and the other had elementary school. 04 live in Recife and all live in an urban area. Most (n = 05) consider themselves to be brown, 05 had family income up to a minimum wage, two more than one salary and none worked. From the process of analyzing the participants’ discourse, two thematic axes emerged: care in prenatal consultations: view of pregnant women and health education in prenatal consultations. The present study made it possible to know how prenatal medical consultations take place and how pregnant adolescents perceive health education.